Finance and Development, June 1985. (Finance and Development; Finance and Development, 1985)
The analysis and adjustment of government expenditure in less developed countries is discussed. A better balance between supply and demand in the public sector can be achieved by raising budgetary revenues, or by cutting budgetary expenditures, or by some combination of both. The IMF devotes considerable attention to assisting countries to make their tax systems more buoyant, to reduce the disincentive effects of taxation, and to administer their tax systems more effectively. Government expenditure policies are often important elements in programs of external adjustment supported by the IMF.